Biomechanics of the sprint start - Harrison, D.; Comyns, T. (coachesinfo.com, 1999)
As noted previously, the sprint start has been the focus of much research over the past number of decades. The "set" position (Baumann, 1976; Mero, Luhtanen and Komi, 1983; Mero, 1988), reaction time (Baumann, 1976; Henry, 1952; Payne & Blader, 1970) and force-time characteristics (Baumann, 1976; Henry, 1952; Mero et al., 1983, Mero, 1988) have been the variables commonly investigated. The aspect that is relevant for review in this thesis is the "set" position. Two studies in particular researched the position of the athlete during the "set" phase of the sprint start: Mero et al. (1983) and Mero (1988). Mero et al. (1983) conducted a biomechanical study on 25 male subjects of varied abilities. Force production, reaction time and "set" position data were collected and analysed. Of particular interest here is the "set" position data. Each subject performed 3 runs over a 10m distance on a tartan type indoor track. The fastest run of each subject was selected for film analysis. Every second frame from the set position up to the third contact phase was analysed using a Vanguard film analyzer, Summagraphics 10 digital board and HP 21MX computer. The mechanical model of the runner was assumed to consist of 14 rigid body segments and the segmental landmarks were marked on the skin with black ink. The subjects were divided into three groups based on sprinting ability. The best sprinters (n=8) were placed in the first group and their mean 100m record time was 10.8 ± 0.30s. The results of the analysis of the best sprinters body positions in "set" can be seen in Table 3. Table 3: Values of the Best Sprinters in "Set" Position Measures Values *(Mero et al, 1983) Front Ankle Angle (q1) 115 ± 90 Rear Ankle Angle (q4) 106 ± 80 Front Knee Angle (q2) 111 ± 90 Rear Knee Angle (q5) 134 ± 140 Front Hip Angle (q3) 41 ± 140 Rear Hip Angle (q6) 80 ± 130 Angle of the Trunk (q7) 29 ± 90 Angle of the Arms(q8) 106 ± 70 Height of the Centre of Gravity (h) 0.605 ± 0.037m Horizontal distance of Centre of Gravity (f) 0.189 ± 0.089m Mero conducted a similar study in 1988 and used eight experienced Finnish male sprinters with a mean 100m record time of 10.79 ± 0.21s. The methodology used was the same as his 1983 study. The results of the analysis of the eight experienced sprinters body positions in "Set" can be seen in Table 4. The values in Table 4 could be referred to as "optimal" values for the "set" position. However, the centre of gravity (C.G.) values, especially the C.G. horizontal distance, differed greatly from previous research. Mero (1988:96) specifically referred to this in the discussion and stated that "...in order to make it (sprint start) more efficient, the body C.G. should be positioned about 0.1m forward." Table 4: Values of the Sprinters in "Set" Position [2] Measures Values *(Mero, 1988) Front Ankle Angle (q1) 94 ± 40 Rear Ankle Angle (q4) 96 ± 80 Front Knee Angle (q2) 96 ± 120 Rear Knee Angle (q5) 126 ± 160 Front Hip Angle (q3) 39 ± 70 Rear Hip Angle (q6) 77 ± 90 Angle of the Trunk (q7) 21 ± 70 Angle of the Arms(q8) 104 ± 80 Height of the Centre of Gravity (h) 0.57 ± 0.04m Horizontal distance of Centre of Gravity (f) 0.29 ± 0.05m In instances when a subject ran a distance in the same time from two of the starting positions, his performance was given one-half point.